2022
DOI: 10.3390/ijms23147972
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefits of Selenium in Hematological Malignancies

Abstract: Supplementing chemotherapy and radiotherapy with selenium has been shown to have benefits against various cancers. This approach has also been shown to alleviate the side effects associated with standard cancer therapies and improve the quality of life in patients. In addition, selenium levels in patients have been correlated with various cancers and have served as a diagnostic marker to track the efficiency of treatments or to determine whether these selenium levels cause or are a result of the disease. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 216 publications
3
4
0
Order By: Relevance
“…Furthermore, it was shown that Se-induced P53 activation may downregulate Bcl-2 and upregulate Bax, which would induce Ehrlich cancer cells to undergo apoptosis (Ramakrishnan et al, 2009). These data agree with earlier research that Se promotes apoptosis in hematological malignancies, (Ehudin et al, 2022) leukemia and lymphoma cells (Wu et al, 2014) and esophageal cancer (Ahsan et al, 2022). It has been reported that, glutathione and Se interacted to form hydrogen selenide, or selenodiglutathione, which causes cytotoxicity in the form of DNA damage, ROS generation and cell death (Kim et al, 2021;Lipinski, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it was shown that Se-induced P53 activation may downregulate Bcl-2 and upregulate Bax, which would induce Ehrlich cancer cells to undergo apoptosis (Ramakrishnan et al, 2009). These data agree with earlier research that Se promotes apoptosis in hematological malignancies, (Ehudin et al, 2022) leukemia and lymphoma cells (Wu et al, 2014) and esophageal cancer (Ahsan et al, 2022). It has been reported that, glutathione and Se interacted to form hydrogen selenide, or selenodiglutathione, which causes cytotoxicity in the form of DNA damage, ROS generation and cell death (Kim et al, 2021;Lipinski, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Historically, Se was considered both a potential toxin and a protective element. Contemporary research has revealed that Se can have both beneficial and harmful effects on organisms, including the nervous system and the heart [ 311 ]. Several human studies have demonstrated that supplementing standard-of-care chemotherapies (such as cisplatin, doxorubicin, cyclophosphamide, and busulfan) with Se (in the form of sodium selenite or organic selenium) reduces toxicity without compromising therapeutic efficacy [ 310 ].…”
Section: Can Antioxidants Act As Pro-oxidants?mentioning
confidence: 99%
“…Accordingly, the deficiency of Se in serum is linked with aberrant immune functions, cancer, cardiac, and inflammatory diseases [42]. Recently, we reviewed the anticancer effects of Se and SeCs alone or in combination with standard therapy (chemo-or radiation) for different hematological malignancies including Leukemias [43]. The supplementation of Se and/or Se-containing food was shown to have chemopreventive effects in animals and humans with some contradictory reports [44].…”
Section: Role Of Se and Seps In Lymphomamentioning
confidence: 99%